2015
DOI: 10.1038/ncomms7008
|View full text |Cite
|
Sign up to set email alerts
|

Dppa3 expression is critical for generation of fully reprogrammed iPS cells and maintenance of Dlk1-Dio3 imprinting

Abstract: Reprogramming of mouse somatic cells into induced pluripotent stem cells (iPSCs) often generates partially reprogrammed iPSCs (pre-iPSCs), low-grade chimera forming iPSCs (lg-iPSCs) and fully reprogrammed, high-grade chimera production competent iPSCs (hg-iPSCs). Lg-iPSC transcriptome analysis revealed misregulated Dlk1-Dio3 cluster gene expression and subsequently the imprinting defect at the Dlk1-Dio3 locus. Here, we show that germ-cell marker Dppa3 is present only in lg-iPSCs and hg-iPSCs, and that inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 43 publications
2
58
0
Order By: Relevance
“…19 Dppa3 only presents in lg-iPSCs and hg-iPSCs but not in pre-iPSCs. In the process of somatic cell reprogramming, three transitional iPSCs are usually generated: partially reprogrammed pre-iPSCs, low-grade chimera iPSCs (lg-iPSCs, completely reprogrammed and only produce lowgrade chimeras), and high-grade chimera iPSCs (hg-iPSCs) that develop high-grade chimeras.…”
Section: Reprogramming Progress Of Somatic Cellsmentioning
confidence: 93%
See 3 more Smart Citations
“…19 Dppa3 only presents in lg-iPSCs and hg-iPSCs but not in pre-iPSCs. In the process of somatic cell reprogramming, three transitional iPSCs are usually generated: partially reprogrammed pre-iPSCs, low-grade chimera iPSCs (lg-iPSCs, completely reprogrammed and only produce lowgrade chimeras), and high-grade chimera iPSCs (hg-iPSCs) that develop high-grade chimeras.…”
Section: Reprogramming Progress Of Somatic Cellsmentioning
confidence: 93%
“…In the process of somatic cell reprogramming, three transitional iPSCs are usually generated: partially reprogrammed pre-iPSCs, low-grade chimera iPSCs (lg-iPSCs, completely reprogrammed and only produce lowgrade chimeras), and high-grade chimera iPSCs (hg-iPSCs) that develop high-grade chimeras. 19 It has been reported that vitamin C (Vc) could improve reprogramming efficiency. Dppa3 expression is activated at day 6 to day 9 during reprogramming earlier than other pluripotent transcriptional factors, such as Oct4 and Sox2.…”
Section: Reprogramming Progress Of Somatic Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, Zscan4, in combination with OSKM, not only reduced the DDR but also markedly promoted the efficiency of iPSC generation, enhanced telomere lengthening as early as 3 days post-infection, and significantly increased the percentage of iPSC lines that gave rise to 'all-iPSC' mice as determined by 4N complementation [63]. In addition, forced expression of the germ cell marker, Dppa3, together with OSKM enhances reprogramming kinetics and generates mostly high-grade iPSCs, as evidenced by the production of iPSC clones with intact Dlk1-Dio3 imprinted locus [64], a locus that when hypermethylated is associated with poor-quality iPSCs [65]. Moreover, the quality of iPSCs is dramatically affected by the specific choice of reprogramming factors [51].…”
Section: Level Of Reprogramming Factorsmentioning
confidence: 95%